To what extent did Anglo-Saxon coins circulate within the Northern Lands? Evidence from the numerical analysis and interpretation of pecking - Melcalf, M. D. (Hikuin, 1985)
As the CNS advances from volume to volume under Professor Brita Maimer’s leadership, the rich opportunities for numismatic analysis directed towards discoveries in the field of monetary history become more nearly practicable. Professor Maimer herself has initiated a debate on one aspect of the evidence, namely the pecking of the coins found in the Northern Lands and in the West Slav countries. Until she drew attention to the possibilities (having herself begun their meticulous recording) it is doubtful whether anyone suspected that such apparently trivial and uninteresting evidence could yield such solid and important results.